Baseline separation of amino acid biomarkers of hepatocellular carcinoma by polyvinylpyrrolidone-filled capillary electrophoresis with light-emitting diode-induced fluorescence in the presence of mixed micelles. Issue 3 (2nd December 2014) - Chen, Yen-Chu; Chang, Po-Ling
Abstract : Separation of amino acid biomarkers could be performed by polyvinylpyrrolidone-filled capillary electrophoresis in the presence of mixed micelles. Abstract : Physiological amino acids (AAs) are important indices for monitoring various diseases, including cancer. This study proposes a polymer-based separation method in the presence of mixed micelles for the determination of AAs by capillary electrophoresis with light-emitting diode-induced fluorescence. The separation of 18 amino acid–cyano[ f ]benzoisoindoles (AA–CBIs) was successfully achieved using a solution of polyvinylpyrrolidone (PVP, 5% w/v, M avg 1 300 000 Da). In addition, we demonstrated that mixed micelles composed of sodium dodecyl sulfate and isopropanol may affect the migration order of the AA–CBIs and greatly improve the speed of separation. With the exception of proline, 21 plasma AA–CBIs, including high isoelectric point AAs (lysine, ornithine, and arginine), were identified by using optimized separation conditions with minimal matrix effects. The results of this study demonstrated the distinct advantages of the proposed method, such as simplicity, high efficiency, and cost-effectiveness. This method has great potential for the diagnosis of several important diseases, including carcinomas, aminoacidopathies, and neurotransmission disorders.